The music industry music in the cloud - Wikstrom, Patrik (Cambridge Polity Press, 2013)
The music industry is going through a period of immense change brought about in part by the digital revolution. What is the role of music in the age pf computers and the internet? How has the music industry been transformed by the economic and technological upheavals of recent years, and how is it likely to change in the future? This thoroughly revised and updated new edition provides an international overview of the music industry and its future prospects in the world of global entertainment. Patrik Wikstrol'm illuminates the workings of the music industry, and captures the dynamics at work in the production of musical culture between the transnational media conglomerates, the independent music companies and the public. New to this second edition are expanded sections on the structure of the music industry, online business models and the links between social media and music. Engaging and comprehensive, the music industry will be a must-read for students and scholars of media and communication studies, cultural studies, popular music, sociology and economics
Introduction: music in the cloud -- A copyright industry -- Inside the music industry -- Music and the media -- Making music -- The social and creative music fan -- Future sounds.
Previous edition: 2009.
Includes bibliographical references (pages 184-197) and index.
Keywords: Music trade -- Technological innovations; Music and the internet; Music -- Social aspects